Christian Mission Based on Dialogue for Promoting Tolerance in the Era of Digitalization and Religious Moderation - Dapot Damanik; Jecson P. Sihombing; Nova Yanti Rumapea; Basa Esterlina Lubis; Siskawati Panjaitan (Jurnal Multidisiplin Sahombu, 2026)
This article examines the concept and implementation of dialogical Christian mission in the context of increasing religious tolerance, rapid digitalization, and the strengthening of religious moderation in contemporary society. The study aims to explore how Christian mission can be carried out through an inclusive, contextual, and relevant dialogical approach in a pluralistic and digitally connected world. Using a qualitative method with a library research approach, data were collected from biblical texts, theological writings, and recent academic publications related to mission, interreligious dialogue, digital culture, and religious moderation. The data were analyzed using content analysis to identify key themes and theological insights.The findings indicate that dialogical mission emphasizes mutual respect, openness, and collaboration rather than confrontation or conversion-oriented approaches. In the digital era, mission practices extend into online platforms, enabling broader engagement while also requiring ethical responsibility and sensitivity to diversity. Furthermore, the integration of religious moderation values strengthens the role of Christian mission as a bridge for peacebuilding and social harmony. This study concludes that dialogical Christian mission represents a relevant and necessary paradigm in the current context, as it promotes constructive engagement, fosters interreligious understanding, and contributes to a more tolerant and cohesive society.